2009
DOI: 10.1021/ja9040785
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Bonding of β-Turn Structure Is Stabilized in D2O

Abstract: The lower critical solution temperature (LCST) of elastin-like polypeptides (ELPs) was investigated as a function of ELP chain length and guest residue chemistry. These measurements were made in both D 2 O and H 2 O. Differences in the LCST values with heavy and light water were correlated with secondary structure formation of the polypeptide chains. Such structural information was obtained by circular dichroism and infrared measurements. Additional thermodynamic data were obtained by differential scanning cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
83
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 62 publications
11
83
0
Order By: Relevance
“…Taken together CD and FTIR analyses confirm that for our hydrophobic oligomers rich in glycine, hydrogen bonding rather than hydrophobicity is the key factor in the stabilization of the collapsed state, as reported in literature for specific ELP-subfamilies. 52,53 On the whole, this work demonstrates that the secondary/tertiary structures are not altered by differing rates of water evaporation and that the aggregation, based on inter-chains recognition, is mainly induced by bridging H-bonds of the polar peptides and altered by hydrophobic hydration and side chains mobility, as specifically shown by the substitution of Val with Leu at the first position of the studied sequences.…”
Section: Discussionmentioning
confidence: 58%
“…Taken together CD and FTIR analyses confirm that for our hydrophobic oligomers rich in glycine, hydrogen bonding rather than hydrophobicity is the key factor in the stabilization of the collapsed state, as reported in literature for specific ELP-subfamilies. 52,53 On the whole, this work demonstrates that the secondary/tertiary structures are not altered by differing rates of water evaporation and that the aggregation, based on inter-chains recognition, is mainly induced by bridging H-bonds of the polar peptides and altered by hydrophobic hydration and side chains mobility, as specifically shown by the substitution of Val with Leu at the first position of the studied sequences.…”
Section: Discussionmentioning
confidence: 58%
“…87,88 By monitoring the time-dependent surface reaction occurring on the photoelectrodes in the presence of water isotopes, the diffuse-reflectance infrared Fourier transform (DRIFT, Fig. 5) technique showed that the intensity of the SCN À ligand remarkably decreased when the water content in the electrolyte (LiI 0.50 M, I 2 50 mM and TBP 0.50 M in ACN; TBP = 4-tert-butylpyridine) increased (from 0 to 5 wt%).…”
Section: Spectroscopic Investigation Of Water-promoted Effectsmentioning
confidence: 99%
“…Similar phenomena were also observed in other thermosensitive polymers. 58 It is noted that the cloud point of PM-2 is 9.9 C lower in D 2 O than in H 2 O, much less pronounced than the cloud point difference (13.3 C) of PH-2. This suggests that the enhanced steric hindrance suppresses the solvent isotopic effect.…”
Section: -55mentioning
confidence: 81%